Isolation and identification of fungi associated with root rot disease in broad bean caused by Rhizoctonia solani (Kuhn)and select the disease suppresser species as biological control agents 2.Induced resistance markers by Trichoderma harzianiumand their relationship with the disease and the plant productivity - Abdullah Abdulkareem Hassan; Maareb Ahmed Awad (Tikrit Journal of Pure Science)
The antagonism ability of the15 species of fungi associated with rot roots disease against the pathogen R.solani showed the growth of fungus T. harzianumwas faster than the pathogen R.s which cover all area of the perti plate with the antagomism degree 1.33. A field experiment was carried out in 2011/2012 in Agriculture College /Tikrit University for the test of the induction of a systemic resistance by T. harzianumagainst root rot disease caused by R.s in three cultivars of broad bean. Shabila cultivar infected with R.s and treated with T. harzianumgave maximum seeds germination (98.67%) compared with 67.67% in the infected and untreated plants. Maximum specific activity of Peroxidase was 10.9 unit/mg protein recorded in the infected and treated (with T. harzianum) local cultivar,while maximum specific activity of β-1,3glucanase was 0.289 unit/mg protein recorded in the uninfected and treated local cultivar,  in the infected and treated Barshlona cultivar, maximum specific activities of Chitinase and Phenyl alanine ammonialyase were 0.074 and 2.089 unit/mg protein, while maximum specific activity of Poly phenol oxidasewas 2.163 unit/mg protein recorded in the infected and treated Shabila cultivar.Maximum total phenols was 19.22 mg/g tissue recorded in the infected and treated local cultivar. T. harzianum reduce the percentage of dead cells from 75.3, 70.0 and 58.3% in the infected local,Shabila and Barshlona cultivars to 20.07,30.0 and 44.4% in the infected and treated these cultivars,respectively.in addition, T.h reduced the percentage of disease severity from, 44.67, 50.67 and 44.67% in the infected local,Shabila and Barshlona cultivars to 14.3, 23.67 and21.93% in the infected and treated these cultivars, respectively, while the productivity of these infected cultivars increased  from 53.7,34.8 and 74.3 g of fresh seeds to 104,68 and 158.8 g of fresh seeds when treated with T. harzianum.